The effect of work setting and demographic factors on caring behaviour among nurses in the public hospitals and public health services, Sabah, Malaysia - Norkiah Arsat; Nik Amin Sahid Nik Lah; Deena Clare Thomas; Sui Fun Soong; Li Tsu Chong; Waidah Sawatan; Norsimah Dasan; Walton Wider (BMC, 2023)
Abstract Background The nursing profession's uniqueness contributes to the development of knowledge, experience, age, education, economy, and position, as well as a unique gender role. Thus, the development and advancement of demographic characteristics of nurses while in this profession influences their caring behavior. Objective The purpose of this study was to determine the effect of work setting and demographic factors on nurses' caring behaviour, as well as the differences in nurses' caring behaviour based on demographic factors between nurses in public hospitals and nurses in public health services in Sabah, Malaysia. Methods This research is a cross-sectional study using the survey method. Data were collected from 3,532 nurses (88.3% response rate) in public hospitals and public health services within Sabah, Malaysia. Data were analysed using two-way ANOVA. Results The two-way ANOVA test revealed no significant impact of the work setting on CB, nor was there a notable interaction between the work setting and demographic factors influencing nurses' CB. However, demographic factors such as gender, age, education, economic status, position, and experience had a significant effect on CB. Conclusion The present research has provided convergent evidence on the effect of demographic factors on nurses caring behavior and the differences in caring behavior based on demographic factors among nurses in public hospitals and public health services in Sabah, Malaysia.